Expans\~ao da área agrícola no Brasil segundo as lavouras permanentes - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Food production remains one of the biggest challenges for humankind in this century, and Brazil is one of the largest food-producing countries that have yet some land for economically or technically profitable farming expansion. Therefore, knowing which areas constitute the Brazilian agricultural frontier is crucial for improving public policies and logistics infrastructure decisions. Data from the Brazilian Institute of Geography and Statistics from 1995 to 2020 were used in this study. We aimed to map and measure the expansion of agricultural areas in Brazil from 1995 to 2020 for permanent crops according to their mesoregions. We applied a four-stage methodology, compared the results of two agglomerative clustering methods, and identified similar mesoregions based on their share trends in the Brazilian agricultural harvesting destined area. Some mesoregions must be highlighted in terms of trend values for their share of the Brazilian agricultural harvesting destined area: Minas' South/Southwest (MG), Triângulo Mineiro/Paranaíba Upstream (MG), Paraense Southwest (PA), Bauru (SP), Woodland Zone (MG), Rio-grandense Northeast (RS), Pernambucano San Francisco (PE) and Minas' North (MG). Other areas such as the Espírito-santense North Coast (ES), Bahia's San Franciscano Valley (BA), Cearense North (CE), Cearense Northwest (CE), Alagoano East (AL), and Paranaense Southeast (PR) constituted a second leading group, and Minas' West (MG), Paraense Northeast (PA), and Doce River Valley (MG) should be emphasized as clusters by themselves. Policy implications are discussed and further research is suggested, especially running top-down analysis targeting microregions or municipalities in the identified mesoregions.
Keywords: Q10; Q15; 330; agricultural frontier; Brazil; permanent crops; Spearman’ s correlation coefficient; clustering